Analysis The Learning Needs of The Paropo Village Community In Tilapia Fish Cultivation - Saragih, Mahfuzi Irwan; Lumbantoruan, Sonya Rosanna (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
This study aims to identify the community’s learning needs in Paropo I Village, Silahisabungan District, related to tilapia fish farming. The research employs a descriptive quantitative method, which describes the condition of subjects or objects based on observable facts without seeking correlations, testing hypotheses, or making predictions. The research sample consisted of 28 fish cage owners in Paropo I Village. Data collection was conducted through observation and the distribution of questionnaires developed to address the research problem. Data analysis techniques included content validation by three experts, validity testing using Aiken’s V, and reliability testing using the Intraclass Correlation Coefficient (ICC). The validity test resulted in a score of 0.89, which is categorized as valid. The reliability test yielded a value of 0.088, which falls into the “good” or reliable category, indicating that the questionnaire is suitable for use. The findings suggest that the community’s learning needs are primarily technical. The highest identified need is the skill to utilize technology to simplify the tilapia harvesting process, cited by 78.6% of respondents. This suggests that technical training especially related to harvesting technology is the primary learning need of the Paropo I Village community in tilapia farming. Keywords: aquaculture, farming, learning community, needs analysis